2022
DOI: 10.1111/ddg.14832
|View full text |Cite
|
Sign up to set email alerts
|

Biologics for pediatric moderate‐to‐severe plaque psoriasis: a systematic review and network meta‐analysis

Abstract: Background and Objectives: To compare the efficacy and safety of biologic treatments for moderate-to-severe pediatric psoriasis approved by the US Food and Drug Administration and European Medicines Agency.Patients and Methods: MEDLINE, Embase, and Cochrane Central Register of Controlled Trials for relevant randomized controlled trials (RCTs) were searched for the identification of eligible RCTs until May 7, 2021. Fixed-effect frequentist network meta-analysis (NMA) was performed with the surface under the cum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
4

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
6
0
4
Order By: Relevance
“…The prevalence of migraine in the pediatric population is estimated 9.1%, rising after puberty. On the other hand, the mean onset age of psoriasis is about 15–30 years and the second peak of onset is 55–60 years while the prevalence of pediatric psoriasis ranges from 0.13% to 2.1% 33 . Both women and men share equal prevalence of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of migraine in the pediatric population is estimated 9.1%, rising after puberty. On the other hand, the mean onset age of psoriasis is about 15–30 years and the second peak of onset is 55–60 years while the prevalence of pediatric psoriasis ranges from 0.13% to 2.1% 33 . Both women and men share equal prevalence of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…2 Seither erschienen in dieser Zeitschrift Publikationen zur Psoriasis in dreistelliger Zahl. In jüngster Zeit umspannen die Themen grundlegende pathophysiologische Aspekte, [3][4][5] therapeutische Ansätze, [6][7][8][9][10][11] epidemiologische Fragen, 12 diagnostische und klinische Entwicklungen, [13][14][15] psychosoziale Aspekte, [16][17][18] bis hin zu Versorgungsforschung und Registerstudien. [19][20][21][22] Empfehlungen zur praktischen Umsetzung neuer Erkenntnisse kulminieren schließlich in Leitlinien.…”
Section: Wo Stehen Wir?unclassified
“…The results of presented clinical trials are similar to those conducted in adult patients. 44 Meta-analysis using SUCRA (surface under cumulative ranking curve) performed by Huang et al 48 showed that among all available clinical trials with biologics in pediatric population (etanercept, adalimumab, ustekinumab, ixekizumab and secukinumab), low dose secukinumab showed the best PASI 90 response (84.7%), followed by ixekizumab (70.8%) at weeks 12–16. Similar analysis was provided by Gohlen at al.…”
Section: Psoriasis and Pediatric Psoriasis - Introductionmentioning
confidence: 99%
“…Meta analysis with such a small number of studies may be underpowered, therefore more published clinical and real-world studies, which are ongoing, would be beneficial for further assessment of secukinumab position in psoriasis treatment in children. 48 , 50 …”
Section: Psoriasis and Pediatric Psoriasis - Introductionmentioning
confidence: 99%